An obstacle for alcohol abstinence - Shakya, DR (Journal of Institute of Medicine Nepal, 2010)
We report a case of ‘alcohol dependence' with anxiety to highlight importance of addressing co morbid psychiatric problem for effective management of alcohol dependence. A 53-year-old lady presented with anxiety for five years, more in the initial days of attempts at abstinence. She had been drinking for thirty years, regularly for ten years and more for the last six years. After developing Hypertension five years back, she had been trying to stop drinking. Upon such attempts, she suffered from restlessness, profuse sweating, tremors and sleeplessness and would feel better only after taking alcohol. Since 2-3 months, after having GI bleed, she was compelled to stop drinking and was struggling in spite of anxiety. Finally, she drank herself to intoxication and her children brought her to psychiatric OPD. With the diagnosis of ‘alcohol dependence syndrome with anxiety disorder', after investigations, she was put on fluoxetine, clonazepam and thiamine-vitamin B supplementation along with psychological interventions to enhance motivation and prevent relapses. She responded well and remained abstinent and asymptomatic at 3-year-follow ups. Blood pressure was also under control. Key words: alcohol, alcohol dependence, anxiety disorder, panic, psychiatric co morbidity. The full text of this paper is available from the Journal of Institute of Medicine website Journal of Institute of Medicine, August, 2009; 31:2 34-36